Optimization of Silicon-rich Silicon Nitride Films for Electron Multiplication in Timed Photon Counters. (2015) - Prodanovic, V.; Chan, H.W.; Smedley, J.; Theulings, A.; Tao, S.; Graaf, H.v.d.; Sarro, P.M.
Abstract: The excellent overall properties of silicon nitride, particularly its mechanical strength and resistance to many etchants, make it a widely used material for microsensors and microactuators. In this paper silicon-rich silicon nitride (SRN) films were investigated as material for ultra-thin transmission dynodes in electron multiplication. These dynodes are a fundamental element of ultrafast timed-photon counters (TiPC). The film properties were tuned to obtain SRN with higher conductivity so to suppress charging up effects, while maintaining or further reducing the low stress level required to fabricate the 20-50 nm thick dynodes. By optimizing low pressure chemical vapour deposition (LPCVD) process, SRN layers with very low compressive stress (± 10 MPa) and very low resistivity (± 10 10 Ohm·m) are obtained.